2006
DOI: 10.1590/s1415-47572006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Transmission analysis of candidate genes for nonsyndromic oral clefts in Brazilian parent-child triads with recurrence

Abstract: Cleft lip and/or palate (CL/P) is a major congenital defect with complex etiology, including multiple genetic and environmental factors. Approximately two thirds of the cases are not accompanied by other anomalies and are called nonsyndromic (NS). In the present study, we performed transmission distortion analysis of the MSX1-CA, TGFB3-CA and MTHFR-C677T polymorphisms in 60 parent-child triads, in which the NS-CL/P affected child had at least one affected parent. No association with genes MSX1 or TGFB3 was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the second phase, the full‐text review was then conducted on the 71 first‐phase selected citations, which lead to the exclusion of 22 studies. In the end of the two phases, 49 studies fulfilled the inclusion criteria (Antunes et al, ; Araújo et al, ; Araujo et al, ; Bagordakis et al, ; Bezerra et al, ; Brandalize et al, ; Brito, Bassi, & Masotti, ; Brito et al, ; Bufalino et al, ; Cardoso et al, ; Choi et al, ; da Silva, Ribeiro, Cooper, Marazita, & Moretti‐Ferreira, ; de Aguiar et al, ; de Aquino et al, a,b; de Souza et al, ; do Rego Borges et al, ; Ehlers Bertoja, Sampaio Alho, De França, Menegotto, & Miriam Robinson, ; Falagan‐Lotsch et al, ; Filézio et al, ; Fontoura, Silva, Granjeiro, & Letra, ; Gaspar et al, ; Jehee et al, ; Küchler et al, ; Letra, Menezes, Granjeiro, & Vieira, ; Letra, Silva, & Menezes, ; Letra et al, a,b; Machado et al, a,b, ; Menezes, Letra, Ruff, Granjeiro, & Vieira, ; Menezes et al, ; Messetti et al, ; Paranaíba et al, ; Passos‐Bueno et al, ; Sabóia et al, ; Souza, Kowalski, Collares, & Félix, ; Souza, Kowalski, Vanz, Giugliani, & Félix, ; Waltrick‐Zambuzzi et al, ; Zucchero et al, ), but only 11 articles were used in the meta‐analysis (Antunes et al, ; Araújo et al, ; Bagordakis et al, ; Brito et al, ; de Aguiar et al, ; do Rego Borges et al, ; Fontoura et al, ; Gaspar et al, ; Paranaíba et al, ;).…”
Section: Resultsmentioning
confidence: 99%
“…In the second phase, the full‐text review was then conducted on the 71 first‐phase selected citations, which lead to the exclusion of 22 studies. In the end of the two phases, 49 studies fulfilled the inclusion criteria (Antunes et al, ; Araújo et al, ; Araujo et al, ; Bagordakis et al, ; Bezerra et al, ; Brandalize et al, ; Brito, Bassi, & Masotti, ; Brito et al, ; Bufalino et al, ; Cardoso et al, ; Choi et al, ; da Silva, Ribeiro, Cooper, Marazita, & Moretti‐Ferreira, ; de Aguiar et al, ; de Aquino et al, a,b; de Souza et al, ; do Rego Borges et al, ; Ehlers Bertoja, Sampaio Alho, De França, Menegotto, & Miriam Robinson, ; Falagan‐Lotsch et al, ; Filézio et al, ; Fontoura, Silva, Granjeiro, & Letra, ; Gaspar et al, ; Jehee et al, ; Küchler et al, ; Letra, Menezes, Granjeiro, & Vieira, ; Letra, Silva, & Menezes, ; Letra et al, a,b; Machado et al, a,b, ; Menezes, Letra, Ruff, Granjeiro, & Vieira, ; Menezes et al, ; Messetti et al, ; Paranaíba et al, ; Passos‐Bueno et al, ; Sabóia et al, ; Souza, Kowalski, Collares, & Félix, ; Souza, Kowalski, Vanz, Giugliani, & Félix, ; Waltrick‐Zambuzzi et al, ; Zucchero et al, ), but only 11 articles were used in the meta‐analysis (Antunes et al, ; Araújo et al, ; Bagordakis et al, ; Brito et al, ; de Aguiar et al, ; do Rego Borges et al, ; Fontoura et al, ; Gaspar et al, ; Paranaíba et al, ;).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies analysed intronic and/or 3′UTR regions using either the case control, the family based or both approaches in combination showing controversial results. In Brazil, a study performed transmission distortion analysis on an intronic CA‐ repeat polymorphism of MSX1 in parent–child triads and found no association between MSX1 and NSCL/P (Silva et al , ). On the other hand, Vieira et al () suggested that MSX1 contributes to clefting in South American populations.…”
Section: Discussionmentioning
confidence: 99%
“…Marker position Alleles rs11726039 11.9 kb upstream from transcription start T/C rs868257 9.2 kb upstream from transcription start C/G rs6446693 6.3 kb upstream from transcription start T/C rs1907998 4.8 kb upstream from transcription start A/G rs6832405 18.0 kb downstream from transcription end G/T significant association between intronic CA repeat polymorphisms and NSCL/P [28]. The MSX1 P147Q polymorphism which was not evaluated in our study, found only in the Asian population with very less frequency, showed contrasting results on the association with NSCL/P [29,30].…”
Section: Snpmentioning
confidence: 99%